Analisis Kualitas Pelayanan Sirkuit Mandalika pada Gelaran WSBK Mandalika 2022 pasca MotoGP Mandalika 2022 (Studi Kasus pada Penonton WSBK Mandalika 2022) - L. Jatmiko Jati; Baiq Rabiatul Adawiyah Kartika Wulan; Stevany Hanalyna Dethan (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to explore in depth the audience's responses to the Mandalika WSBK 2022 event regarding the quality of service and strategies implemented by the committee to ensure orderly flow of spectators before and after the Mandalika WSBK 2022 event. This research uses a qualitative approach with a case study type of research. The selection of research subjects was carried out using a purposive sampling technique, namely the Mandalika WSBK 2022 spectators from Lombok and Yogyakarta who came to watch directly at the Lombok Mandalika Circuit. Methods of data collection is done by using interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data display, and verification as well as drawing conclusions. Data validity test was carried out using the triangulation method. Based on the results of this study, it can be concluded that there is an increase in the quality of service for the Mandalika circuit at the Mandalika WSBK 2022 event after the Mandalika MotoGP 2022. This can be evidenced by the various responses of respondents to the dimensions of service quality: Reability, the existence of accuracy in serving the audience with service standards clear. Responsiveness, the complaints that existed during the Mandalika MotoGP 2022 have been well responded to by the circuit officials. Assurance, the responses to the complaints that existed during the Mandalika MotoGP 2022 made the audience's level of trust increase in the quality of service, so that respondents wanted to return to witness the WSBK 2023 event. Attention, the convenience provided by circuit officials such as venues new parking and pedestrian paths that have been installed with conblocks. Tangible evidence, the convenience provided in the spectator service process, the convenience of a new parking lot for spectators, the increasing cleanliness of portable toilets, and the quality of the Mandalika Circuit asphalt has been perfected.